Genetic mapping reveals a candidate gene CmoFL1 controlling fruit length in pumpkin - Zhou, Yimei; Zhao, Meng; Shen, Qinghui; Zhang, Mengyi; Wang, Chenhao; Zhang, Yutong; Yang, Qinrong; Bo, Yongming; Hu, Zhongyuan; Yang, Jinghua; Zhang, Mingfang; Lyu, Xiaolong (Frontiers in Plant Science, 2024)
Fruit length (FL) is an important economical trait that affects fruit yield and appearance.Pumpkin (Cucurbita moschata Duch) contains a wealth genetic variation in fruit length.However, the natural variation underlying differences in pumpkin fruit length remains unclear. In this study, we constructed a F2 segregate population using KG1 producing long fruit and MBF producing short fruit as parents to identify the candidate gene for fruit length. By bulked segregant analysis (BSA-seq) and Kompetitive Allele-Specific PCR (KASP) approach of fine mapping, we obtained a 50.77 kb candidate region on chromosome 14 associated with the fruit length. Then, based on sequence variation, gene expression and promoter activity analyses, we identified a candidate gene (CmoFL1) encoding E3 ubiquitin ligase in this region may account for the variation of fruit length. One SNP variation in promoter of CmoFL1 changed the GT1CONSENSUS, and DUAL-LUC assay revealed that this variation significantly affected the promoter activity of CmoFL1. RNA-seq analysis indicated that CmoFL1 might associated with the cell division process and negatively regulate fruit length. Collectively, our work identifies an important allelic affecting fruit length, and provides a target gene manipulating fruit length in future pumpkin breeding.